MUATAN PENDIDIKAN ANTIKORUPSI DALAM MATA KULIAH PENGKAJIAN DAN APRESIASI PUISI DI JAWA TENGAH DAN YOGYAKARTA - Chafit Ulya; Nugraheni Eko W; Yant Mujiyanto (Jurusan Tadris Bahasa Indonesia, 2016)
This study aims to describe and explain the content of anti-corruption education in the study and appreciation of poetry in Central Java and Yogyakarta. The object of this research is five universities in Central Java and Yogyakarta, ie UNS, UAD, UMP, Unsoed, and Unikal. The content of anti-corruption education obtained through interviews with the lecturer of the course poem in five universities. Data were collected and analyzed by an interactive model. The results obtained from this study are as follows. (1) The values of anti-corruption education has been internalized into the course study and appreciation of poetry; (2) The value of anti-corruption education that internalized is still general and not concretely lead to anti-corruption values; (3) The value of anti-corruption education that internalized through poems containing the noble values of character education.